Dataset of the molecular dynamics simulations of bilayers consisting of short amyloidogenic peptide VDSWNVLVAG from Bgl2p–glucantransferase of S. cerevisiae cell wall - Glyakina, Anna V. (Data Brief, 2016)
The amyloidogenic peptide VDSWNVLVAG from Bgl2p–glucantransferase of Saccharomyces cerevisiae cell wall and its modifying analog VESWNVLVAG were taken for the construction of four types of bilayers which differ by orientation of the peptides in the layers and of the layers relative to each other. These bilayers were used as starting models for the molecular dynamics (MD) at three charge states (neutral, pH3, and pH5). The changes of the fraction of secondary structure during 1 ns simulations were received for 96 MD trajectories. The data article contains the necessary information for the construction of models of β-strands organization in the oligomer structure. These results were used in the associated research article “Structural model of amyloid fibrils for amyloidogenic peptide from Bgl2p–glucantransferase of S. cerevisiae cell wall and its modifying analog. New morphology of amyloid fibrils” (Selivanova et al., 2016) [1].